LEGAL PROTECTION OF FAMOUS TRADEMARK DISPUTES REGISTERED UNDER THE LAW (CASE OF POLO BY RALPH LAUREN TRADEMARK DISPUTE) - Tati Sri Hardina (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
: Trademarks are signs in the form of images, names, words, letters, numbers, color arrangements, or combinations of these elements that have distinguishing power and are used in trading activities for goods or services. A well-known brand is a brand that has a high reputation. This brand has the power of radiance that is mesmerizing and attractive, so that the type of goods under the brand immediately raises a touch of familiarity (familiar) and mythical ties (mythical contect). The research method used is normative juridical, namely library law research conducted by examining library materials or secondary data. Protection of trademark rights in Indonesia constitutively adheres to the first to file system, first to file trademark protection system or constitutive system is a system of protection of a trademark in which the party who first applied for registration to the trademark office, then become the first party who has rights to the trademark. Of course, without exception, every application for trademark registration must pass the substantive examination process by the Trademark Examiner. In the substantive examination, it will be decided whether the person or legal entity is entitled to the trademark rights they apply for or the application for trademark rights is rejected. In order for the trademark to be protected by law.